Peningkatan Jiwa Wirausaha Santri, Pendampingan Rebranding Produk dan Pemasaran Daring di Ponpes Raiyatul Husnan Bondowoso - Agus Mahar Mahardiyanto; Fajar Wahyu Prianto; Abdul Fatah; Dwi Perwitasari Wiryaningtyas; N. Ari Subagio; Mohammad Saleh (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2025)
IMPROVING THE ENTREPRENEURIAL SPIRIT OF SANTRI, ASSISTANCE IN PRODUCT REBRANDING AND ONLINE MARKETING AT THE RAIYATUL HUSNAN ISLAMIC BOARDING SCHOOL, BONDOWOSO. The purpose of this activity is to unravel partner problems in the form of digital-based marketing strategies and the weak entrepreneurial spirit of the students managing the Raihan bottled drinking water (AMDK) business unit owned by Pesantren Raiyatul Husnan. The method in this service is in the form of mentoring, training, and equipping students with Business Model Canvas (BMC) Analysis and digitalisation material which is expected to help students in the entrepreneurial world. The results of the training showed a significant increase in students' understanding of BMC Analysis and digitalisation, where before the training 80% of students did not understand BMC and afterwards students who did not understand BMC and digital decreased to only 20%. Continuation of training needs to be done so that students dare to try entrepreneurship and find a business that suits their potential.